Coordinating cross-country congestion management - Friedrich Kunz; Alexander Zerrahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We employ a detailed two-stage model to simulate the operation of the Central Eastern European electricity market and network. Implementing different cases of coordination in congestion management between national transmission system operators, numerical results show the beneficial impact of closer cooperation. Specific steps comprise the sharing of network and dispatch information, cross-border counter-trading, and multilateral redispatch in a flow-based congestion management framework. Efficiency gains are accompanied by distributional effects. Closer economic cooperation becomes especially relevant against the background of changing spatial generation patterns, deeper international integration ofnational systems, and spillovers of national developments to adjacent systems
Keywords: C63; L51; L94; 330; electricity; congestion management; network modeling; Europe